Peran Guru BK di Era Digital: Mempertahankan Nilai Budaya dalam Menghadapi Revolusi Industri - Bunda, Thessia Permata; F, Firman; Sukma, Dina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The era of digitalisation has brought significant changes in the education system, which requires adaptation of the role of counselling teachers to bridge the gap between technological advancement and preservation of cultural values. The methodology used in this study is qualitative with a documentation or literature study approach. Counselling teachers need to develop digital competencies while maintaining an approach grounded in local cultural values. The implementation of a counselling programme that combines traditional methods with digital platforms proved effective in achieving this goal. The research also revealed the importance of collaboration between counselling teachers, parents and local communities in building a supportive educational ecosystem. The main contribution of this research is to present a strategic framework for counselling teachers in integrating digital technology into their services while maintaining and strengthening local cultural values. The implications of this research point to the need to develop digital competency improvement programmes for counselling teachers that remain grounded in local wisdom.